(untitled) (Biological Sciences - PJSIR, 2002)
In this paper it is considered to study the two pH-Renewal Process cases by Constructing the vector Markov process, because of the dense of Shi’s formula in the set of non-negative random variables , the results are explicit and meaningful for the problems connected with the failure and replacement.